STATEHOOD, LANGUAGE, AND ALPHABET: A KAZAKHSTAN CASE STUDY - TAJIBAEVA, Saule; KOZYREV, Timur (CENTRAL ASIA AND THE CAUCASUS, 2007)
As a young state, just 15 years old, the Republic of Kazakhstan is still developing its national identity and civic spirit formula. The absence or, at least, precariousness of the basis on which a civic nation united by a shared system of values could emerge is a popular topic of discussion. More often than not this problem is seen through the prism of ethnic relations, which, in turn, are reduced to the “autochthonous population”-the Russian speakers dichotomy.1 Today, this dichotomy is still dominated by a language issue of great symbolic significance. Reform of the alphabet came to the fore as one of the aspects of the country’s state language problem in the wake of President Nazarbaev’s speech at the 12th Session of the Assembly of the Peoples of Kazakhstan. It seems, however, that vague and often confusing interpretations of everything related to the concepts of ethnos, nation, nationalism, national state, and civil society are the real stumbling blocks. We have inherited this from the Soviet times; today, this part of Soviet legacy causes misunderstandings fraught with conflicts, at least among politicians. We intend to outline our approaches to a few of the most burning issues within the statehood-language-alphabet triangle.Today, ethnic relations in Kazakhstan are associated with the relations between the “locals” and the “Russian speakers.” In fact, the situation is not that simple: not only is Kazakhstani society divided, the state-forming Kazakh ethnos is too. There is a vast cultural-psychological gap between the urban Kazakhs, who speak Russian and are integrated into the post-Soviet (to a certain extent Western-oriented) culture that uses the Russian language, and the population that speaks the Kazakh tongue and is guided by traditional values. The objective social distinctions between the two groups make it even harder to bridge the cultural-psychological gap. The “rupture syndrome” of the Kazakh cultural and spiritual expanse presents the main obstacle on the road toward forming a common civil self-awareness among the Kazakhstanis. Below we shall dwell on this in greater detail The far from simple relations between the “locals” and the “Russian-speaking population” are also pertinent, but in order to bring the two groups together into a real (rather than proclaimed) political entity, the Kazakhs themselves must achieve spiritual unification and national revival lest the entity known as the Kazakhstanis is left without a supporting structure and a firm foundation on which their statehood can be built. We shall demonstrate below that the ethnic structure does not contradict the idea of the nation’s civic model.